Musculoskeletal Issues in Pediatric Burn Patients - Phillips, William A. (Seminars in Plastic Surgery, 2024)
A burn injury affects virtually every organ system. The purpose of this article is to review musculoskeletal issues in children with burn injuries. Both acute and long-term problems will be discussed. A low threshold to consult a pediatric orthopaedist is recommended.
Keywords: burn; musculoskeletal; child